Mre11 and Blm-Dependent Formation of ALT-Like Telomeres in Ku-Deficient Ustilago maydis - Yu, Eun Young (Public Library of Science, 2015)

(untitled) (PLoS Genet)
A subset of human cancer cells uses a specialized, aberrant recombination pathway known as ALT to maintain telomeres, which in these cells are characterized by complex aberrations including length heterogeneity, high levels of unpaired C-strand, and accumulation of extra-chromosomal telomere repeats (ECTR). These phenotypes have not been recapitulated in any standard budding or fission yeast mutant. We found that eliminating Ku70 or Ku80 in the yeast-like fungus Ustilago maydis results initially in all the characteristic telomere aberrations of ALT cancer cells, including C-circles, a highly specific marker of ALT. Subsequently the ku mutants experience permanent G2 cell cycle arrest, accompanied by loss of telomere repeats from chromosome ends and even more drastic accumulation of very short ECTRs (vsECTRs). The deletion of atr1 or chk1 rescued the lethality of the ku mutant, and “trapped” the telomere aberrations in the early ALT-like stage. Telomere abnormalities are telomerase-independent, but dramatically suppressed by deletion of mre11 or blm, suggesting major roles for these factors in the induction of the ALT pathway. In contrast, removal of other DNA damage response and repair factors such as Rad51 has disparate effects on the ALT phenotypes, suggesting that these factors process ALT intermediates or products. Notably, the antagonism of Ku and Mre11 in the induction of ALT is reminiscent of their roles in DSB resection, in which Blm is also known to play a key role. We suggest that an aberrant resection reaction may constitute an early trigger for ALT telomeres, and that the outcomes of ALT are distinct from DSB because of the unique telomere nucleoprotein structure.